2012
DOI: 10.1098/rstb.2011.0249
|View full text |Cite
|
Sign up to set email alerts
|

Recombination rate variation and speciation: theoretical predictions and empirical results from rabbits and mice

Abstract: Recently diverged taxa may continue to exchange genes. A number of models of speciation with gene flow propose that the frequency of gene exchange will be lower in genomic regions of low recombination and that these regions will therefore be more differentiated. However, several population-genetic models that focus on selection at linked sites also predict greater differentiation in regions of low recombination simply as a result of faster sorting of ancestral alleles even in the absence of gene flow. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
485
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(523 citation statements)
references
References 113 publications
34
485
4
Order By: Relevance
“…It should be noted that the centromeric region is expected to show reduced recombination in general (for example, Carneiro et al, 2009;Geraldes et al, 2011;Nachman and Payseur, 2012), and that this has been documented for metacentric chromosomes in the house mouse (Dumas and Britton-Davidian, 2002). As the extent of genetic differentiation in the three chromosome regions was essentially the same among races sharing the same disposition of chromosomes (3.8 or 3.14 and 8.11), as well as within races, it seems unlikely that solely a 'centromeric effect' is responsible for the significant divergence observed at proximal loci between karyotypic groups (that is, 3.8 versus 3.14 and 8.11).…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsementioning
confidence: 90%
See 1 more Smart Citation
“…It should be noted that the centromeric region is expected to show reduced recombination in general (for example, Carneiro et al, 2009;Geraldes et al, 2011;Nachman and Payseur, 2012), and that this has been documented for metacentric chromosomes in the house mouse (Dumas and Britton-Davidian, 2002). As the extent of genetic differentiation in the three chromosome regions was essentially the same among races sharing the same disposition of chromosomes (3.8 or 3.14 and 8.11), as well as within races, it seems unlikely that solely a 'centromeric effect' is responsible for the significant divergence observed at proximal loci between karyotypic groups (that is, 3.8 versus 3.14 and 8.11).…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsementioning
confidence: 90%
“…Thus, Panithanarak et al (2004) compared chromosomes that did and did not differ between chromosomal races in Northern Italy and showed that centromeric regions of rearranged chromosomes showed less introgression than non-rearranged chromosomes. Such a study would be worthwhile on the Madeiran mice, to rule out the possibility that the reduced gene flow associated with proximal markers of metacentric 3.8 is a purely centromeric effect, rather than an impact of the chromosomal rearrangement (Carneiro et al, 2009;Geraldes et al, 2011;Nachman and Payseur, 2012). Such work is currently being carried out, using a suite of centromeric microsatellites that includes three loci per chromosome (total 60 loci: three for each of the 19 autosomes, plus three on the X chromosome).…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsementioning
confidence: 99%
“…Reduced recombination, in general, can contribute to divergence during the speciation process (reviewed in Nachman & Payseur [58]). Further, genomic scans and experimental approaches have identified regions with greater differentiation than expected under neutrality that are clustered but not associated with inversions (reviewed in earlier studies [1,59,60]).…”
Section: Future Directionsmentioning
confidence: 99%
“…Several nonexclusive factors can potentially contribute to the genetic mosaic that is created during the process of population divergence and speciation. These include exogenous and/or endogenous drivers of divergent selection (Rundell and Price, 2009;Schluter, 2009); genetic drift (Ohta, 1992); variable mutation and recombination rates (Hedrick, 2005;Noor and Feder, 2006;Nachman and Payseur, 2012); chromosomal structure (Rieseberg, 2001;Strasburg et al, 2012); or the genomic distribution and size effects of genes under selection (Orr, 2005;Rogers and Bernatchez, 2007;Michel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most controversial issues, from both theoretical expectations and empirical results, is the creation and maintenance/ growth of the genomic regions of divergence during speciation with gene flow (Hoffmann and Rieseberg, 2008;Feder and Nosil, 2010;White et al, 2010;Yeaman and Whitlock, 2011;Nachman and Payseur, 2012;Nosil and Feder, 2012;Feder et al, 2012b;Narum et al, 2013). Via (2009Via ( , 2012, proposed that strong divergent selection acting on a few loci generates an inter-population process, which she called divergence hitchhiking (DH), that is characterized by reduced inter-population recombination and gene flow.…”
Section: Introductionmentioning
confidence: 99%